RESPON SISWA TERHADAP PEMBELAJARAN INQUIRY-BASED STEM UNTUK MENINGKATKAN LITERASI STEM MELALUI PEMBUATAN PLASTIK RAMAH LINGKUNGAN - Wardani, Mela Aprilian; Erman, Erman (Jurnal Dedikasi Pendidikan, 2025)
This study aims to find out and analyze students' responses to inquiry-based STEM learning to improve students' STEM literacy through making environmentally friendly plastics. This research was conducted in one of the junior high schools in the city of Surabaya with a sampling technique using purposive sampling. The data collection technique was carried out using a student response questionnaire to the application of the learning model carried out. The data obtained will be analyzed by calculating the percentage of each student's answer so that positive and negative student responses are obtained. Based on the results of the study, it was stated that the students' responses showed positive results for all indicators. In the indicator of the ability to identify problems, the percentage of student responses to the indicator of ability to solve problems using STEM scored 75.83%, the percentage of student responses to the indicator of ability to determine new knowledge scored 77.92%, the percentage of student responses to the indicator of ability to apply STEM concepts scored 72.08%, the percentage of student responses to the indicator of ability to solve problems using STEM scored 73.33%, the percentage of student responses to the indicator of ability to communicate related to STEM scored 75.83%, while the indicator of the ability to make the right decisions based on STEM scored 74.17%. Thus, it can be concluded that the student response is in the good category.  The inquiry-based STEM model can be used as one of the learning models that can improve students' STEM literacy.